High-income ZIP codes in New York City demonstrate higher case rates during off-peak COVID-19 waves - Tung, Steven T. L.; Perveen, Mosammat M.; Wohlars, Kirsten N.; Promisloff, Robert A.; Lee-Wong, Mary F.; Szema, Anthony M. (Frontiers in Public Health, 2024)
Introduction: Our study explores how New York City (NYC) communities of various socioeconomic statuses were uniquely impacted by the COVID-19 pandemic. Methods: New York City ZIP codes were stratified into three bins by median income: high-income, middle-income, and low-income. Case, hospitalization, and death rates obtained from NYCHealth were compared for the period between March 2020 and April 2022.Results: COVID-19 transmission rates among high-income populations during off-peak waves were higher than transmission rates among low-income populations. Hospitalization rates among lowincome populations were higher during off-peak waves despite a lower transmission rate. Death rates during both off-peak and peak waves were higher for low-income ZIP codes.Discussion: This study presents evidence that while high-income areas had higher transmission rates during off-peak periods, low-income areas suffered greater adverse outcomes in terms of hospitalization and death rates. The importance of this study is that it focuses on the social inequalities that were amplified by the pandemic.